DESA DAMAI SLAMIC ECONOMIC SPIRITUAL GUIDANCE - Irmansyah, Irmansyah; Adi Prayitno; Nurfahmi Idris; Febi Andriyan; Romi Fahillah; Irawan Fakhrudin Mz; Syaiful Bahri (Bengkulu Institute, 2024)
Spiritual guidance is an activity to sow and cultivate public awareness of the economic values ​​contained in Islam. From the long history of conventional economic structures, it can be concluded that it is called economics because humans always want to feel comfortable, without any shortages or disturbances that will befall them. Such concerns will certainly never exist. This activity will also reveal the essence of economics in Islam. As a religion that is approved by Allah..ar-Rohmaan ar-Rohiim, it is certain that all aspects related to it such as economic affairs tend to be positive. The spirituality of Islamic economics is a spirit that is manifested from the purity and tranquility of the Islamic religion itself. So, if the purpose of life in Islam is to worship Allah ar-Rohmaan ar-Rohiim, then the economy truly refers to that purpose. If the sharia outlined by Islam as a provision for the afterlife, it is certain that the values ​​embedded in the economy are subject (sharia compliance) to the intended order. Thus it can be understood together that Islamic economic spirituality is a building of awareness of Muslims, including their literacy process of Islamic economics. Spiritual needs are a dimension of life that can determine the meaning,purpose,suffering and death of person.